2020
DOI: 10.1089/dna.2019.5221
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum and Lysosomal Quality Control of Four Nonsense Mutants of Iduronate 2-Sulfatase Linked to Hunter's Syndrome

Abstract: Hunter's syndrome (mucopolysaccharidosis type II) is a rare X-linked lysosomal storage disorder caused by mutations in the iduronate-2-sulfatase (IDS) gene. Motivated by the case of a child affected by this syndrome, we compared the intracellular fate of wild-type IDS (IDS WT ) and four nonsense mutations of IDS (IDS L482X , IDS Y452X , IDS R443X , and IDS W337X ) generating progressively shorter forms of IDS associated with mild to severe forms of the disease. Our analyses revealed formylation of all forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…These results are compatible with previous reports (describing results of studies on single MPS types) which indicated enhanced expression of genes coding for proteasomal proteins in MPS I (Khalid et al, 2016), rapid proteasomal degradation of mutant forms of iduronate-2-sulfatase in MPS II (Osaki et al, 2018;Marazza et al, 2020), rapid proteasomal degradation of mutant N-sulfoglucosamine sulfhydrolase (Muschol et al, 2011) and cysteine string protein α (CSPα) (Sambri et al, 2017), as well as elevated levels of the 19S proteasomal subunit (Beard et al, 2017) in MPS IIIA, and rapid proteasomal degradation of synaptophysin in MPS IIIB (Vitry et al, 2009). Nevertheless, results presented in this report provided global picture of proteasomal changes in all MPS types.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are compatible with previous reports (describing results of studies on single MPS types) which indicated enhanced expression of genes coding for proteasomal proteins in MPS I (Khalid et al, 2016), rapid proteasomal degradation of mutant forms of iduronate-2-sulfatase in MPS II (Osaki et al, 2018;Marazza et al, 2020), rapid proteasomal degradation of mutant N-sulfoglucosamine sulfhydrolase (Muschol et al, 2011) and cysteine string protein α (CSPα) (Sambri et al, 2017), as well as elevated levels of the 19S proteasomal subunit (Beard et al, 2017) in MPS IIIA, and rapid proteasomal degradation of synaptophysin in MPS IIIB (Vitry et al, 2009). Nevertheless, results presented in this report provided global picture of proteasomal changes in all MPS types.…”
Section: Discussionsupporting
confidence: 93%
“…Since proteasome is a protein-degrading cellular machinery, it is unlikely that it might be involved directly in GAG metabolism. However, it was reported that defective lysosomal enzymes, the products of mutated genes which are primary causes of MPS, are misfolded and therefore intensively ubiquitinated and extensively degraded by proteasomes (Vitry et al, 2009;Muschol et al, 2011;Osaki et al, 2018;Marazza et al, 2020). Therefore, any residual activity of the defective enzyme may be further reduced due to low stability of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, rescue of IDS mutants by the inhibition of ERAD may be sufficient to attenuate the pathology in patients with MPS II. One of the severe-type truncated mutants, W337X, was also reported to be degraded by the ERAD pathway, although the lysosomal localization and enzyme activity of the mutant under the inhibition of ERAD have not been determined [43]. Although further investigations are needed, other MPS II-related IDS mutants may also cause loss of function through degradation via the ERAD pathway.…”
Section: Degradation Of Mutant Ids By the Er-associated Degradation (Erad) Systemmentioning
confidence: 99%